Dextran production by Lactobacillus sakei MN1 coincides with reduced autoagglutination, biofilm formation and epithelial cell adhesion. (15th July 2017) - Nácher-Vázquez, Montserrat; Iturria, Iñaki; Zarour, Kenza; Mohedano, Maria Luz; Aznar, Rosa; Pardo, Miguel Ángel; López, Paloma
Highlights: Lb. sakei MN1 and Lc. mesenteroides RTF10 synthesise dextran from sucrose. During dextran synthesis Lb. sakei, aggregates, adheres and forms biofilm. During dextran synthesis Lc. mesenteroides does not, aggregate, adhere or form biofilm. L. sakei colonised zebrafish gut, reducing the lethal activity of a Vibrio sp. Reduction of adhesion to epithelial cells did not affect the anti-vibrio activity. Abstract: In this work we have investigated two dextran-producing lactic acid bacteria, Lactobacillus sakei MN1 and Leuconostoc mesenteroides RTF10, isolated from fermented meat products. These bacteria synthesise dextran when sucrose, but not glucose, is present in the growth medium. The influence of dextran on bacterial aggregation, adhesion and biofilm formation was investigated in cultures challenged with sucrose or glucose. For Lb. sakei MN1, the synthesis of the dextran drastically impaired the three processes; in contrast it had no effect on Lc. mesenteroides RTF10. Therefore, the influence of dextran on probiotic properties of Lb. sakei MN1 was tested in vivo using gnotobiotic zebrafish models. The bacterium efficiently colonised the fish gut and inhibited the killing activity of Vibrio anguillarum NB10[pOT11]. Furthermore, under conditions of dextran synthesis, the adhesion of Lb. sakei MN1 to the epithelial cells decreased, without greatly affecting its anti V. anguillarum activity.